Exclusive growth? Rapidly increasing top incomes amid low national growth in South Africa - Ihsaan Bassier; Ingrid Woolard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Despite South Africa's need for inclusive economic growth, we find that the income trajectories of the rich continue to diverge from the rest of the income distribution. We combine household survey data and tax data (which, unlike household survey data, includes accurate data for the very rich) to investigate the patterns of income growth over the period 2003 to 2017. We find that the gap between the stagnant middle and the top end of the income distribution widened between 2003 and 2017. We also show that the divergence was partly driven by high returns to capital for those with top incomes.
Keywords: D31; H24; 330; top incomes; income distribution; tax data